Kinetic and Theoretical Investigation of Iron(III)‐Catalyzed Silane Chlorination. Issue 3 (9th December 2015) - Savela, Risto; Grénman, Henrik; Sundelin, Heidi; Norrby, Per‐Ola; Yu. Murzin, Dmitry; Leino, Reko
Abstract: A highly versatile, robust, and efficient methodology for chlorination of silanes, methoxysilanes and silanols using low loadings of FeCl3 or Fe(acac)3 as the catalyst in the presence of 1–1.5 equivalents of acetyl chloride as the chlorine source was recently developed. The aim of the present paper is to evaluate and derive the reaction mechanisms involved in this reaction by calculating substrates, intermediates, products, and selected transition states, as well as by employing mathematical modeling of the reaction kinetics. The results obtained required reconsideration of the originally proposed overall reaction mechanism. Based on the kinetic and molecular modeling, a new revised reaction mechanism was developed giving a very good correspondence between the experimental data and calculations. Abstract : Do the math : The reaction mechanisms of iron‐catalyzed chlorination of silanes are investigated by DFT calculations, as well as by employing mathematical modeling of the reaction kinetics. A new revised reaction mechanism is developed giving a very good correspondence between the experimental data and calculations.